THE FUTURE OF BUSINESS EDUCATION IN NIGERIAN UNIVERSITIES: EXPLORING HYBRID TEACHING MODEL AND AI TECHNOLOGY FOR ENHANCED SKILLS DEVELOPMENT OF STUDENTS (NAU Journal of Technology and Vocational Education, 2026)
The future of business education in Nigerian universities is increasingly shaped by technological advancements and innovative teaching models. This study explored the role of the hybrid teaching model and artificial intelligence (AI) technology in enhancing students’ skills development in South-East Nigerian Universities. Two research questions and two null hypotheses guided the study. Using a survey research design, data were collected from 92 business educators across universities in South East Nigeria that offer business education programme. There was no sampling.  The instrument for data collection was a 26-item structured questionnaire titled “Adoption of Hybrid Learning Models and AI Technology for Enhanced Skills Development (AHLMAITESD). The face validity of the instrument was ascertained by three experts in the field of education. Pilot testing method as used in determining the reliability of the instrument, and data analyzed using the Cronbach alpha formula resulted in correlation coefficient values of.88 and.79 for clusters B1 to B2 respectively, with an overall coefficient index of .84 obtained. Data were collected from business educators across universities by the researcher with the help of six research assistants. Statistical mean, standard deviation and independent t-test were used for data analysis. Findings reveal that while business educators agree on the influence of hybrid teaching model in improving students’ skills development, they disagree on their adoption of AI-powered hybrid teaching model for enhancing skills development of their students. Based on the findings of this study, the researcher concluded that that business educators are not overly adopting AI-powered hybrid teaching model in enhancing skills development of students. It was recommended among others that; Heads of department of business education programmes in South-East Nigerian universities should organize regular workshops and training programmes to equip business educators with the necessary skills and knowledge to effectively integrate AI-powered hybrid teaching model. This will improve its adoption by business educators in enhancing skills development of their students.
Keywords: Business Education; Hybrid Teaching Model; Artificial Intelligence; Skills Development